Numerical Study of Surface Flow for Ahmed Body in Crosswind Conditions - Duy, Pham Van; Anh, Le Dinh; Truong, Dinh Cong; Hung, Tran The; Minh, Do Van (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2024)
This study investigates standard vehicles' flow behavior and drag during crosswind conditions by a numerical approach. The model is a half-scaled Ahmed body with a slant angle of 25°. Reynolds Average Navier-Stokes equations with turbulent model k-ω SST is applied to solve Navier Stokes equation by discrete method. Experimental data validated the numerical results at the same flow conditions. The results indicated that the model's drag increases with yaw angles, which is connected with the development of the longitudinal vortex on the windward side. However, the lift coefficient and pressure drag acting on the slant showed a maximum value at a yaw angle of around 35° before they dropped again. The drop of those coefficients results in the moving upward of the longitudinal vortex above the slant. The complex vortex structures around the base in both cross-sectional and symmetric planes are analyzed. The skin-friction pattern and pressure distribution on the slant are exposed to understand the effect of the yaw angle on aerodynamic forces.